Yangsheng 養生 as 'making a living' in the Zhuangzi. Issue 1 (2nd January 2023) - Turner, Kevin J.
ABSTRACT: The story of the butcher Pao Ding is one of the best known from the Zhuangzi 莊子. The key concept in this story is yangsheng 養生. This has been understood as involving the preservation of life through various methods of cultivation. However, one insightful perspective has yet to be considered: work. This article sets the stage for understanding yangsheng in terms of work by appealing to Western and Eastern understandings thereof. It then locates the Zhuangzi in contemporary discourse on yangsheng showing that it rejects that concerned with regulating the senses in search of life and accepts that concerned with the activities constitutive of livelihoods. This article then analyzes the relationship between sheng 生 and xing 性 to show that yangsheng is best understood as 'making a living' that emerges in the process of individual and collective lives as they unfold in various contexts.